Clinical Signs of Impending Death in Cancer Patients. (23rd April 2014) - Hui, David; dos Santos, Renata; Chisholm, Gary; Bansal, Swati; Silva, Thiago Buosi; Kilgore, Kelly; Crovador, Camila Souza; Yu, Xiaoying; Swartz, Michael D.; Perez‐Cruz, Pedro Emilio; Leite, Raphael de Almeida; Nascimento, Maria Salete de Angelis; et al.
Abstract : Background: The physical signs of impending death have not been well characterized in cancer patients. A better understanding of these signs may improve the ability of clinicians to diagnose impending death. We examined the frequency and onset of 10 bedside physical signs and their diagnostic performance for impending death. Methods: We systematically documented 10 physical signs every 12 hours from admission to death or discharge in 357 consecutive patients with advanced cancer admitted to two acute palliative care units. We examined the frequency and median onset of each sign from death backward and calculated their likelihood ratios (LRs) associated with death within 3 days. Results: In total, 203 of 357 patients (52 of 151 in the U.S., 151 of 206 in Brazil) died. Decreased level of consciousness, Palliative Performance Scale ≤20%, and dysphagia of liquids appeared at high frequency and >3 days before death and had low specificity (<90%) and positive LR (<5) for impending death. In contrast, apnea periods, Cheyne‐Stokes breathing, death rattle, peripheral cyanosis, pulselessness of radial artery, respiration with mandibular movement, and decreased urine output occurred mostly in the last 3 days of life and at lower frequency. Five of these signs had high specificity (>95%) and positive LRs for death within 3 days, including pulselessness of radial artery (positive LR: 15.6; 95% confidence interval [CI]: 13.7–17.4), respiration with mandibular movement (positive LR: 10; 95% CI: 9.1–10.9), decreased urine output (positive LR: 15.2; 95% CI: 13.4–17.1), Cheyne‐Stokes breathing (positive LR: 12.4; 95% CI: 10.8–13.9), and death rattle (positive LR: 9; 95% CI: 8.1–9.8). Conclusion: We identified highly specific physical signs associated with death within 3 days among cancer patients. Abstract : The authors examined the frequency and onset of 10 bedside physical signs and their diagnostic performance for impending death. They identified highly specific physical signs associated with death within 3 days among cancer patients. Abstract : 摘要 背景 . 癌症患者中濒死的生理症状尚未完全明确。更好的理解这些症状可能会提高临床医生判断濒死的能力。我们分析了10种床边生理症状的出现时间、概率及其对濒死的诊断性能。 方法 . 针对357例入住两个急性姑息性治疗科室的晚期癌症患者，我们每12小时1次系统性记录从住院到死亡或出院过程中的10种生理症状。从死亡起回溯分析每种症状出现的中位时间与频率，计算其与3天内死亡相关的似然比（LR）。 结果 . 总体上，357例患者中有203例（美国151例中死亡52例，巴西206例中死亡151例）死亡。死亡前意识水平下降、姑息体力状态评分≤20%以及液体吞咽困难发生率很高，持续时间>3天，对濒死的特异性较低（<90%），LR阳性（<5）。相反，呼吸暂停周期、潮式呼吸、临终前喉鸣音、末梢性紫绀、桡动脉脉搏消失、下颌运动式呼吸、尿量减少多见于临终前最后3天，但发生率较低。临终前3天 内上述症状中有5项对死亡的特异性很高（>95%）且LR阳性，包括桡动脉脉搏消失[阳性LR：15.6；95%可信区间（CI）：13.7∼17.4]、下颌运动式呼吸（阳性LR：10；95% CI：9.1∼10.9）、尿量减少（阳性LR：15.2；95% CI：13.4∼17.1）、潮式呼吸（阳性LR：12.4；95% CI：10.8∼13.9）、临终前喉鸣音（阳性LR：9；95% CI：8.1∼9.8）。 结论 . 我们发现了癌症患者中临终前3天内死亡相关的高度特异性生理症状。 The Oncologist 2014;19:681–687